ANALISIS PENGELOLAAN LAPORAN KEUANGAN DANA BOSP MELALUI SISTEM INFORMASI PENGELOLAAN KEUANGAN SEKOLAH - Khusna Nur Hidayati; Agung Slamet Prasetyo; Priyastiwi Priyastiwi (Jurnal Akuntansi dan Bisnis, 2025)
This research aims to digitize the BOSP Financial Report of SMA Negeri 1 Yogyakarta through the School Financial Management Information System website. This is motivated by the condition of the SPJ administration which is still processed semi-manually, the wrong nominal input into the bank deposit receipt which results in failed transfers, and incorrect tax transfers (over/underpayment of taxes). The method used is qualitative with data collection techniques through observation, interviews, and documentation. Research procedures include: 1) making a flowchart of the financial transaction process, 2) designing the output format of the financial accountability letter, 3) simulating the school financial management information system accompanied by a programmer, 4) testing on three different users. The test results show that the financial management of SMA Negeri 1 Yogyakarta through the School Financial Management Information System produces output documentation of SPJ completeness automatically and can present real-time financial reports. It is expected that the School Financial Management Information System can improve the accuracy and achievement of the realization of BOSP fund absorption.